2010
DOI: 10.1111/j.1365-2966.2010.17455.x
|View full text |Cite
|
Sign up to set email alerts
|

The entropy core in galaxy clusters: numerical and physical effects in cosmological grid simulations

Abstract: A flat distribution of low gas entropy in the core region of galaxy clusters is a feature commonly found in Eulerian cosmological simulations, at variance with most standard simulations of smoothed particle hydrodynamics fashion. From the literature, it is still unclear whether this difference is entirely due to numerical artefacts (e.g. spurious transfer from gravitational energy to thermal energy), physical mechanisms (e.g. enhanced mixing in Eulerian codes) or a mixture of both. This issue is related to man… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 105 publications
5
34
0
Order By: Relevance
“…Apart from slightly larger normalization, it has been found that there is significantly higher (flatter) core entropy in AMR case as a result of the hydrodynamical processes that are resolved in the code (e.g. shocks and mixing motions) (Mitchell et al 2009;Vazza 2011;Power et al 2014). On the other hand, observations find deviations from the predicted entropy profile at small radii (Pratt et al 2010;Eckert et al 2013a) as well as large radii (Eckert et al 2013a;Su et al 2015).…”
Section: Introductionmentioning
confidence: 78%
“…Apart from slightly larger normalization, it has been found that there is significantly higher (flatter) core entropy in AMR case as a result of the hydrodynamical processes that are resolved in the code (e.g. shocks and mixing motions) (Mitchell et al 2009;Vazza 2011;Power et al 2014). On the other hand, observations find deviations from the predicted entropy profile at small radii (Pratt et al 2010;Eckert et al 2013a) as well as large radii (Eckert et al 2013a;Su et al 2015).…”
Section: Introductionmentioning
confidence: 78%
“…In reality, AGN activity may drive small-scale turbulent motions around the core region of clusters (e.g. Heinz et al 2006;Scannapieco & Bruggen 2009;Dubois et al 2010Vazza 2011), while the interplay of a tangled magnetic field and cosmic rays is expected to inject chaotic motions at very small scales, via instabilites in the ICM (Parrish & Stone 2008;Quataert 2008;Ruskowsky & Oh 2010;McCourt et al 2011;Ruszkowsky et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Agertz et al 2007) and the different stratification of gas entropy within the inner cluster atmosphere, which in turn affects the stability to convective motions in the ICM (e.g. Wadsley et al 2008;Mitchell et al 2008;Springel 2010;Vazza 2011).…”
Section: Radial Distribution Of the Turbulent Energy In The Icmmentioning
confidence: 99%
“…1 for our three different clusters. We note that the flat entropy cores could be related to numerical effects, such as artificial heating caused by softening effects or N-body noise, as investigated by Vazza (2011). However, the effect is limited to the very centre of the clusters and does not affect our study of RPS, as we have no trajectories of galaxies passing through the innermost region.…”
Section: Isolated Galaxy and Cluster Modelsmentioning
confidence: 97%